Exposure to second-hand smoke and support for smoke-free policies in an urban district in Lagos, Nigeria - Chiamaka Queen Ikpe; Tope Olubodun; Olukemi Ololade Odukoya (Tobacco Induced Diseases, 2018)
Background Second hand smoke (SHS) is a danger to human health with no safe levels of exposure. With the recently enacted state-wide anti-smoking law, this study aimed to examine the self-reported exposure to SHS and assess the support for smoke-free policies among residents of Oriade Local Council Development Area, an urban district in Lagos.